Analisis Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan (Studi Pada PT. Bank Rakyat Indonesia, Tbk. Periode 2018-2021) - Karnila Ali; Febiyanto; Reza Gunarti (Jurnal Manajemen DIVERSIFIKASI, 2024)
The financial industry such as banking is a source of tax revenue in Indonesia. The purpose of this study is to examine the effect of Good Corporate Governance on financial performance. The concept that BRI can apply to realize good corporate governance is applied to the idea of ​​Good Corporate Governance (GCG). The type of research used is a type of quantitative research. This study uses secondary data obtained from the annual report of the Bank Rakyat Indonesia (BRI) company. The company performance used in this study uses ROA as a measure and as a variable. The sample used in this research is the annual report of PT. Bri period 2018-2021. Data were analyzed using multiple regression analysis with the help of the SPSS 25 program. The results of this study showed (1). The Board of Directors influences financial performance (2). The Board of Commissioners has an influence on financial performance.